2006
DOI: 10.1016/j.nuclphysb.2006.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Twisted tori and fluxes: A no go theorem for Lie groups of weak holonomy

Abstract: In this paper we prove the theorem that there exists no 7-dimensional Lie group manifold G of weak G 2 holonomy. We actually prove a stronger statement, namely that there exists no 7-dimensional Lie group with negative definite Ricci tensor Ric IJ . This result rules out (supersymmetric and non-supersymmetric) Freund-Rubin solutions of M -theory of the form AdS 4 × G and compactifications with nontrivial 4-form fluxes of Englert type on an internal group manifold G. A particular class of such backgrounds which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…In [61] it was observed that if the embedding tensor is restricted to the representation (20, 2) in (4.119), upon an N = 4 truncation, the resulting theory coincides with the N = 4 gauged supergravity mentioned above, describing Type IIB superstring compactified on a T 6 /Z 2orientifold in the presence of RR and NS-NS 3-form fluxes F (3) , H (3) . One can apply a similar analysis to the study of M-theory flux-compactifications [88][89][90][91], see also [95,96]. In the toroidal compactification of eleven-dimensional supergravity to fourdimensions the relevant group with respect to which to branch the E 7(7) -representations is…”
Section: Gaugings From Flux Compactificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [61] it was observed that if the embedding tensor is restricted to the representation (20, 2) in (4.119), upon an N = 4 truncation, the resulting theory coincides with the N = 4 gauged supergravity mentioned above, describing Type IIB superstring compactified on a T 6 /Z 2orientifold in the presence of RR and NS-NS 3-form fluxes F (3) , H (3) . One can apply a similar analysis to the study of M-theory flux-compactifications [88][89][90][91], see also [95,96]. In the toroidal compactification of eleven-dimensional supergravity to fourdimensions the relevant group with respect to which to branch the E 7(7) -representations is…”
Section: Gaugings From Flux Compactificationsmentioning
confidence: 99%
“…Here we briefly recall the definition of a quaternionic Kähler manifold 96 M QK [163,172,271,273] and fix the notations. A quaternionic-Kähler manifold M QK of real dimension 4n H is defined as a Riemannian manifold whose holonomy group is contained inside SU(2) × USp(2n H ).…”
Section: Quaternionic Kähler Manifoldsmentioning
confidence: 99%
“…As one sees these conditions just coincide with what we named Englert equation: it suffices to set Y [3] = and identify μ 4 = −12e. In [9], together with M. Trigiante I showed that the existence of a form satisfying eqs. (1.7) is equivalent to the definition, introduced in [10], of manifolds M 7 of weak G 2 -holonomy.…”
Section: Introductionmentioning
confidence: 97%
“…The background equation (33) implies that the four dimensional spacetime is Minkowski and that the group under consideration is "flat" [22], i.e.…”
Section: Scherk-schwarz Reduction With No Fluxmentioning
confidence: 99%
“…In this paper, we study Scherk-Schwarz [22] 2 reductions of D = 11 supergravity with background flux [25,26,27,28,29,30,31,32,33,34,35] within the context of the formalism developed in [1]. The Scherk-Schwarz flux compactification has principally been studied from a four-dimensional gauge algebra perspective by associating background fields to particular representations in the GL (7) decomposition of the 912 representation of E 7 (7) in which the embedding tensor lives.…”
Section: Introductionmentioning
confidence: 99%